Building on Soft Foundations – New Possibilities for Controlling Hybrid Photovoltaic Architectures - Franklin,JB; Downing,JM; Giuliani,F; Ryan,MP; McLachlan,MA (Advanced Energy Materials, 2012)
Here we outline a methodology for the deposition of a highly crystalline transparent conductive metal oxide (ZnO) onto a functionalised organic thin film poly (3-hexylthiophene, P3HT) without degradation of the microstructural, optical or electronic properties of the organic layer. To confirm the absence of damage we have assembled a simple bilayer photovoltaic (PV) device. The processing methodology has enabled us to demonstrate hybrid photovoltaic (h-PV) device formation in the conventional architecture for the first time. The compatibility of this novel low temperature processing route with π-conjugated molecular materials has tremendous potential for applications including electron accepting layers and optical spacers in organic PVs and light emitting diodes, as transparent electrodes and all future devices reliant on flexible substrates.